Fine particulate matter source apportionment of the brown haze in Cape Town - Wicking-Baird, Mark Christopher (Department of Social Development, 2024)
"Brown Haze" is a term used to describe a brown-coloured smog found predominantly in the wintertime in the Cape Town region. It occurs. mostly from April to September due to strong) temperature inversions and windless conditions that can occur during these months, which lead to the build-up of pollutants emitted into the atmosphere. The haze extends over most of the Cape Metropolitan Area, but does not appear, by visual observation, to be of uniform intensity. It shifts, depending on the direction of any light wind. The haze is normally most intense in the morning and then lifts and disperses as the day continues. The haze has a strong degrading effect on visibility which is immediately apparent to the general public and to tourists. Capetonians are especially proud of the natural beauty of their city, and the haze is increasingly eroding this pride. Also of concern is the effect on the tourist industry which i$ projected to be Cape Town's most important economic growth area. The haze is also cause for concern to residents because of health risks that may accompany the visible air pollution. Small particles, largely responsible for the haze, can also have serious respiratory effects if their concentration is sufficiently high. The same conditions that are conducive to the formation of a haze are also conducive to the accumulation of gases which are invisible, but if sufficiently concentrated can have unpleasant health and odour effects.